Southwest Airlines flight 1248 (C) - Diermeier, Daniel, (SAGE Knowledge. Cases., 2017)
After the company's first aviation fatality, Southwest Airlines's CEO is faced with new and difficult decisions. The alacrity and compassion that characterized the company's response serves as a paradigm for any organization facing a future crisis situation.